Distribusi Foraminifera Bentonik Hidup dalam Hubungannya dengan Sedimen Dasar Laut di Selat Sumba, Nusa Tenggara Timur - Putra, Purna Sulastya; Hari Nugroho, Septriono (Jurnal Geologi dan Sumberdaya Mineral, 2019)
Marine geological survey of Ekspedisi Widya Nusantara (EWIN) LIPI 2016 was conducted by using RV Baruna Jaya VIII in the Sumba Waters from 4 to 26 August 2016. One of the aim of this survey is to understand the sea floor surface sediment characteristics and its influence to the benthic foraminifera distribution. Seven sediment samples were collected from sea floor surface in Sumba Strait, at the different location and depth using grabbing method with box corer. The samples have analyzed for the foraminifera content, sediment grain size, organic matter and carbonate content, and chemical element by XRF method. The living benthic foraminifera distribution increase to the east of the research area, which have higher content of the organic material and Fe, Rb, Zr, Zn and Sr elements in the sediment. The benthic foraminifera distribution most abundance founded at the depth of 800-1000 m with sediment types are sandy coarse silt  to sandy very coarse silt.Keywords: Benthic foraminifera, distribution, sea floor sediment, Sumba Strait. DOI: 10.33332/jgsm.2019.v20.1.17-26